Silver Man’s Self-Concept in Carrying Out His Social Interaction at Simpang Glugur Medan City - Stepy Maria Tio Daina Sihombing; Amir Purba; Dewi Kurniawati (Journal of Social Interactions and Humanities, 2023)
This research aims to analyze self-concept, social interaction in the context of interpersonal communication, and the role of the self-concept of silver people in Simpang Glugur, Medan City. The research methodology uses a qualitative approach. Data analysis uses the Miles and Huberman technique which includes data collection, data condensation, data display, conclusion drawing verifying. The results of the research show that the self-concept of silver humans in carrying out social interactions at Simpang Glugur, Medan City is divided into two self-concepts, The self-concept that silver humans have influences how silver humans carry out their social interactions in the context of interpersonal communication.